Cultural signals in understanding firt-year student engagement: How can universities become more culturally sensitive? The case of a rural South African university - Mkhize, J. S.; Ramrathan, L. (South African Journal of Higher Education, 2021)
High levels of student engagement, particularly in first-year university students are associated with a wide range of educational practices and conditions including students’ social and academic integration into the institutions of higher education. These educational practices link student engagement with students’ performance to students’ academic achievement leading to graduate throughputs. The study sought to understand first-year student experiences of the university’s ability to provide an academic environment that is conducive and responsive to learning for students with unique characteristics. Data were generated from first-year students enrolled for a Bachelor of Education degree in a rural South African University using focus group interviews with students that were purposively selected from this cohort using areas of specialization as the criteria. Also, one-on-one interviews were conducted with students that had performed well in their examinations as well as those that did not perform so well. The results revealed that students’ cultural orientations are a precursor of how student would thrive in their academic journey and that students’ cultural repertoires influence the extent to which students integrate and engage both academically and socially into the university environment. In this article, we argue that students’ cultural orientations have implications in their academic performance and social integration in their first year of study at university. This article contributes to the ongoing research agenda of student engagement, academic success, first-year student experience and throughput employing students’ cultural signals as another dimension to understand such critical phenomena.